Food as a basic food practice of existence and a transfer channel of additional symbolic meanings to the corporal structure - Burlachuk, L.; Shebanova, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article provides by a theoretical digression of changes "relations of human to food" and of changes strategies "eating behavior" in the cultural and historical development.It is shown that food in human culture acquires the binary code. On the one hand, it serves as the base practice of existence that satisfies the primary (biological, vital needs). Food for human archaic culture allowed him satisfy his hunger sated, and thus to have pleasure. The food was coded as "food = satiety = pleasure". Food has acquired the meaning of "magic saturation" (satiety). On the other hand, food serves the channel broadcasts of additional symbolic values in the human body structure and is a mediator between matter and spirit, which is expressed in a variety of rituals (food traditions, rituals, etc.), the sense of which was directed to establish of transcendental links between the food, human and the spirit.The food represents a earliest forms of property which guarantees the existence and eating behavior (by both external and internal activity) is the earliest forms of control and to use this "property".Is noted that the strategy of eating behavior are the foundation of stratification that had an ethnic, the gender and social (the class) character. Revealed that development of civilization helped to change the eating behavior strategies.
Keywords: food; eating behavior of human physicality; everyday reality